ANALISIS PENERAPAN METODE PEMBERIAN TUGAS (RESITASI) TERHADAP KEMANDIRIAN BELAJAR SISWA DI KELAS VIII SMP NEGERI 1 SIRANDORUNG - Nopin T Sondang Siagian; Rahmatika Elindra; Nunik Ardiana (JURNAL MathEdu (Mathematic Education Journal), 2022)
This study aims to determine how the application of the assignment method (recitation) to the independent learning of students in Class VIII SMP Negeri 1 Sirandorung. This research was conducted at SMP Negeri 1 Sirandorung. The research method used is a qualitative method. The informants in this study were as many as 35 students. The data and data sources used are primary and secondary data sources. Data collection techniques used are observation, questionnaires, interviews, tests and documentation. The data validity technique used is triangulation. Data analysis techniques are data reduction, data presentation and conclusion drawing. In accordance with the results of the research carried out, it is known that the results of learning observations using the assignment method are 75.00. This achievement shows the application of the assignment method is in the good category. From the questionnaire distributed to 35 students, it is known that the highest score is 95 and the lowest score is 60. While the achievement of the average score of the questionnaire distributed is 80.07 which is in the very strong category. Then it is known as many as 14 students who have a strong learning independence category or 40% of the number of class VIII students then as many as 21 students or 60% who have a very strong category. This shows that through the application of the recitation method, student learning independence is very strong.